Effect of Lycoperdon pyriforme fungus extracts on fungi isolated from burns of recumbent patients in Baquba Teaching Hospital / Diyala (Journal of the College of Basic Education, 2022)
Fungi contaminated with burns were isolated and diagnosed from patients in Baquba Teaching Hospital - Burn Hall of Diyala Governorate during the period from October 3, 2021 to December 30, 2021, where 54 samples were collected. The percentage of samples contaminated with fungi was 92.59%, 50 samples, while the percentage of non-contaminated samples With fungi 7.41% by 4 samples. The results of the isolation showed the presence of 229 fungal isolates of the genus Aspergillus. The results of the diagnosis showed the identification of four species, which are Aspergillus niger, and the number of isolates was 96. As for the fungus Aspergillus fumigatus, the number of isolates was 87, followed by the fungus Aspergillus parasiticus, where the number of isolates was 37, and Aspergillus ochraceus, which was 9. The results also show that the fungus Aspergillus niger recorded the highest rate of frequency and appearance, which was 41.92% and 42%, respectively, while the lowest rate of frequency and appearance was for Aspergillus ochraceus, which amounted to 3.93% and the percentage of appearance was 10%. The results of the study showed the effect of three types of extracts for the fungus Lycoperdon pereform which is hot water and alcoholic ethanol and methanol that all the extracts were effective in inhibiting the growth of fungi isolated from burns, but the hot water extract had the least effect as it was found that its effect increases with increasing concentration of the extract, which reached 88.88% over 75%. As for the ethanolic and methanol extract only, the percentage of inhibition for the growth of the isolated fungi was 100% and for all concentrations, which was 25%, 50%, 75% compared to the control treatment.